2014
DOI: 10.1017/s1368980014002171
|View full text |Cite
|
Sign up to set email alerts
|

Parental motivation to change body weight in young overweight children

Abstract: Objective: To determine what factors are associated with parental motivation to change body weight in overweight children. Design: Cross-sectional study. Setting: Dunedin, New Zealand. Subjects: Two hundred and seventy-one children aged 4-8 years, recruited in primary and secondary care, were identified as overweight (BMI ≥ 85th percentile) after screening. Parents completed questionnaires on demographics; motivation to improve diet, physical activity and weight; perception and concern about weight; parenting;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
(59 reference statements)
1
4
0
Order By: Relevance
“…Our results are broadly consistent with other studies showing a mismatch between how parents perceive their child's weight and objective weight measures [14]. Studies from Portugal, the Netherlands and New Zealand have demonstrated similar disparities for young children; 17% of overweight Portuguese 2-6 year-olds, 15% of overweight Dutch 5-year-olds, and 42% of overweight 2-8 year-old New Zealanders, were perceived as overweight by their parents [27][28][29].…”
Section: Main Findingssupporting
confidence: 91%
“…Our results are broadly consistent with other studies showing a mismatch between how parents perceive their child's weight and objective weight measures [14]. Studies from Portugal, the Netherlands and New Zealand have demonstrated similar disparities for young children; 17% of overweight Portuguese 2-6 year-olds, 15% of overweight Dutch 5-year-olds, and 42% of overweight 2-8 year-old New Zealanders, were perceived as overweight by their parents [27][28][29].…”
Section: Main Findingssupporting
confidence: 91%
“…Another explanation for the differences between the weight categories could be that children with morbid obesity might be more aware of a healthy and active lifestyle than children with less severe obesity after being referred to the obesity center for treatment and might be more motivated to improve PA and reduce ST already before the start of the intervention. The results of the study from Taylor et al (2014) showed that motivation (to change body weight and PA habits) was higher among parents from children with more severe overweight [ 27 ]. For the present study, it could be that the children with morbid obesity (and their parents) were more concerned about their health and/or experienced already mental or physical problems after being referred by the youth healthcare division or general practitioners.…”
Section: Discussionmentioning
confidence: 99%
“…Amotivation describes an individual’s lack of any compelling reason for a behavior. In the clinical setting, a better understanding of motivational factors could potentially assist physicians who are aiming to promote healthy behaviors in their patients [ 15 17 ]. Motivation-based interventions, in complement to SDT, can then be employed to promote behavior change, with the potential to lead to weight loss [ 18 ].…”
Section: Introductionmentioning
confidence: 99%